ASUHAN KEPERAWATAN MOBILISASI DINI PADA NY. N DENGAN POST SC DI RSUD HJ. ANNA LASMANAH BANJARNEGARA - Firman Arif Fadilah; Eko Sari Ajiningtyas; Dwi Astuti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Sectio caesarea is a medical procedure that is needed to assist in childbirth with certain indications, both due to maternal health problems and the condition of the fetus. Post SC early mobilization is an activity of the mother or activities carried out by the mother immediately after the SC delivery process. Mobilization exercises aim to make the patient able to concentrate or focus his mind on the movements being performed rather than the pain experienced. Purpose of the study is to describe early mobilization nursing care for post sc mothers. This study used a case study method with respondents giving birth with sc. Using 3 instruments, namely observation sheets, interview sheets and the Gordon assessment format. This research was carried out in Kutabawa Village for 3 days. After 3 days of action, the client can carry out early mobilization independently. Early mobilization that the author has taught clients can speed up the recovery process in post sc mothers.